The Effect of Cognitive-Behavioral Therapy on Acromegalics After a 9-Month Follow-Up - Kunzler, Lia Silvia; Naves, Luciana Ansaneli; Casulari, Luiz Augusto (Frontiers in Endocrinology, 2019)
Introduction The quality of life of acromegalics is compromised. Treatment with the “Think healthy and feel the difference” technique has been described as effective in the improvement of the quality of life of these patients in the short term. However, its effectiveness in the long term needs to be evaluated. Objective The purpose of this study was to evaluate whether the good results obtained from the “Think healthy and feel the difference” technique in the short term persists in the long term, after the end of the treatment. Method This is a non-randomized longitudinal study with twenty-three acromegalic divided into two groups: an intervention group with ten patients and a control group with thirteen patients. The intervention itself covered nine group sessions, organized weekly, using a technique called “Think healthy and feel the difference.” The control group did not receive the aforementioned treatment. The Short Form 36 Question Health Survey (SF-36) and the Beck Depression Inventory were administered before the sessions began, at the end of the nine therapy sessions and at the nine-month follow-up. Results At the end of the treatment, the results of the SF-36 showed improvement in the mental health of the intervention group compared to the control group. The effects of therapy were maintained at the nine-month follow-up. Conclusion Cognitive-behavioral therapy, applied in a group format, can improve the quality of life of acromegalic patients in the short- and long-term.